Decision Making Factor Of Young Woman As Commercial Sex Worker - Muhammad Reza; Amsal Amri (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
Prostitution as a social problem is seen in the form of prostitution, such as the practice of selling sexual services or so-called commercial sex workers. Decision making becomes a common thing taken or done in the face of various problems to survive. Commercial sex workers are part of an occupation that has an intimate relationship outside of marriage characterized by the satisfaction of various people involving several men who are done for money and used as a source of income. The objective of this research is to know the factor of the cause of young woman becoming commercial sex worker, how prostitution in adolescent life in Lhokseumawe city, and decision process of adolescent girl as commercial sex worker. The method used is descriptive qualitative. Data collection techniques using observation, interview, and documentation. Young women make the decision to become commercial sex workers due to internal factors and external factors. Internal factors include about the economy. External factors include lifestyle, environment, and historical lives of respondents. Every teenager who has little economic power must be able to control themselves in association, be a teenager who has the quality and quantity for the entire community amazed and proud of young women who have multi talents. Qualitative research approach symbolic interactionism George Herbert Mead. The subject of 5 teenage girls commercial sex workers, aged 18-25 years. The results showed that the decision-making process of each subject is influenced by the foundations of decision-making include: physical, emotional, rational, practical, interpersonal and environmental. Each subject has different decision-making basics. However, the lack of experience and opportunities the subject has has resulted in weak skills in viewing and making choices. So in making the decision the subject only see one opportunity or opportunity that can be taken. That is to be a commercial sex worker.Keywords: Decision Making, Young Women, Commercial Sex Workers